2006
DOI: 10.1016/j.eplepsyres.2006.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the LGI/Epitempin gene family in sporadic and familial lateral temporal lobe epilepsy

Abstract: Mutations in the LGI1/Epitempin gene cause autosomal dominant lateral temporal lobe epilepsy (ADLTE), a partial epilepsy characterized by the presence of auditory seizures. However, not all the pedigrees with a phenotype consistent with ADLTE show mutations in LGI1/Epitempin, or evidence for linkage to the 10q24 locus. Other authors as well as ourselves have found an internal repeat (EPTP, pfam# PF03736) that allowed the identification of three other genes sharing a sequence and structural similarity with LGI1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…The role of defective LGI1 in the origin of the epileptic focus from the lateral temporal lobe remains unclear, and efforts to identify the genetic defect in LGI1 ‐negative ADPEAF patients have hitherto been inconclusive. In fact, genetic studies failed to disclose mutations in any of the several candidate genes evolutionarily or functionally related to LGI1 , whereas the small size of most LGI1 ‐negative ADPEAF families has generally hampered gene mapping through linkage analysis. Finally, identification of additional genes underlying this disorder might be made particularly challenging by the fact that a fraction of the LGI1 ‐negative families may have a complex genetic architecture, thus implicating the oligogenic inheritance of multiple low‐penetrance mutations.…”
mentioning
confidence: 99%
“…The role of defective LGI1 in the origin of the epileptic focus from the lateral temporal lobe remains unclear, and efforts to identify the genetic defect in LGI1 ‐negative ADPEAF patients have hitherto been inconclusive. In fact, genetic studies failed to disclose mutations in any of the several candidate genes evolutionarily or functionally related to LGI1 , whereas the small size of most LGI1 ‐negative ADPEAF families has generally hampered gene mapping through linkage analysis. Finally, identification of additional genes underlying this disorder might be made particularly challenging by the fact that a fraction of the LGI1 ‐negative families may have a complex genetic architecture, thus implicating the oligogenic inheritance of multiple low‐penetrance mutations.…”
mentioning
confidence: 99%
“…By immunohistochemical analysis, we demonstrated that the LGI1 protein, which contains several leucine‐rich repeats, is expressed ubiquitously in the neuronal cell compartment of the brain. Moreover, we have provided evidence for genetic heterogeneity within this disorder, several other families with a phenotype consistent with this type of epilepsy lacking mutations in the LGI1 gene (Michelucci et al., ; Ayerdi‐Izquierdo et al., ).…”
Section: Neurogenetic Disorders In the Basque Countrymentioning
confidence: 99%
“…However, not all the pedigrees with a phenotype consistent with ADLTE show mutations in LGI1/Epitempin gene or have evidence for linkage to the 10q24 locus. (13) Previous studies have shown evidence of association of LGI-4 polymorphism with Benign Familial Infantile Convulsions (BFIC) (9) and childhood absence epilepsy. (14) In this study, we tested whether genetic variations in the GABRG2 and LGI-4 gene confers susceptibility to idiopathic epilepsy and febrile seizures or not in Indian population.…”
mentioning
confidence: 99%